If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3 + 6x) = 20 (3 * 6 + 6x * 6) = 20 (18 + 36x) = 20 Solving 18 + 36x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 36x = 20 + -18 Combine like terms: 18 + -18 = 0 0 + 36x = 20 + -18 36x = 20 + -18 Combine like terms: 20 + -18 = 2 36x = 2 Divide each side by '36'. x = 0.05555555556 Simplifying x = 0.05555555556
| m+5=m-6 | | 5+5=6+9 | | 2.2+5.2-7.3= | | (8+3i)-(2+4i)=0 | | -k+14=-4-2(2k-3) | | -3(2x+5)=-3 | | -4(4x+3)=2(5-8x)-22 | | x+23y=-15 | | 9q+5(8+2q)=0 | | 7+4(6+2-7)= | | 9q+5(8+2q)= | | 5a-9=29 | | -35x+42= | | f(x)=3x^2-18x+1 | | .666x=180 | | 5/8x=17 | | x^3-x^2-75/8=0 | | 5/8t=-10 | | y-4=5(x+3) | | 2(x+4)=-36 | | 3y=2y+24 | | 8x^3+8x^2-75=0 | | 3*5+5y=45 | | -(9n-2)-15-c-n= | | X^2+12=25 | | 3.5x+5= | | 7w+1=-4w | | 7(7x+1)=49x+7t | | 3x+5*0=45 | | Y=2x-66 | | 4+x=30 | | y=-8-11 |